General strength index and adiposity as a measure of health-related physical fitness among children and adolescents from Bogotá, Colombia: The FUPRECOL study (2016)
Objective: The purposes were: a) to generate normative values of general strength index (GSI) scores of 9- to 17.9-year-olds; and b) to describe the associations between GSI and adiposity markers in healthy schoolchildren from Bogotá, Colombia. Methods: From a total of 7,268 Colombian children and adolescents (age 9-17.9 years) taking part in the FUPRECOL study (4,139, 57% girls). A GSI score were measured using handgrip strength and standing long jump. Each of these variables was standardized as follows: standardized value = (value = mean)/SD. The GSI score was calculated as the mean of the two standardized scores and recoded into quartiles Q1 (low GSI) to Q4 (high GSI). Body mass index (BMI), waist circumference (WC), waist-to-height ratio (WtHR) and percentage body fat (%BF) by electrical bioimpedance analysis were measured such as adiposity markers. Results: The average age was 12.8 ± 2.3 years. It can be seen that the results for the boys were generally more homogeneous than for the girls, regarding muscular fitness. There was also a trend towards increased muscular strength in the boys as their age increased, whereas the girls showed stability or a slight increase in GSI. In contrast, there was an inverse relationship between the GSI and WtHR (r = - 0,280, p less than 0,01) and %BF (r = -0,327, p less than 0,01) in males. Participants with Q4 (high GSI), compared to those in with Q1 (low GSI), had significantly lower levels of BMI, WC, WtHR and %BF. Conclusion: This paper presents the first sex- and age-specific percentiles for general strength index score among Colombian children and adolescents aged 9-17.9 years. The testing of muscle strength at early ages should be included in health-monitoring systems. © 2016, Grupo Aula Medica S.A. All rights reserverd.